Extraction of Capsaicin from the Millet Pepper by Natural Deep Eutectic Solvent - Fang, Beibei; Huang, Maoan; Liu, Qing; Zhai, Xuchun; Yang, Chengli; Li, Dali (Fine Chemical Engineering, 2025)
This study aimed to design a Natural Deep Eutectic Solvent (NADES) for extracting capsaicin from the millet pepper (Capsicum annuum L.). Results demonstrated that NADES3 composed of choline chloride and citric acid (2 : 1 molar ratio) yielded 4.23 mg capsaicin per gram of pepper under optimized conditions (30% water content, 20 mL/g liquid-solid ratio, 20 min ultrasound). Post-enrichment with AB-8 macroporous resin, capsaicin recovery efficiency reached 87.66%. Molecular dynamics simulation revealed a stronger NADES3/capsaicin interaction compared to ethanol/capsaicin, indicating that capsaicin exhibits better homogeneous dispersion in NADES3 than in ethanol. Moreover, the recyclable NADES3 could be reused at least 4 times, showing that the proposed extraction method was eco-friendly. Thus, this study will serve as a reference for the future application of NADES in extracting other alkaloids, both in laboratory and industrial settings.